Factors associated with cytomegalovirus antigenemia in patients with rheumatic disease: A retrospective study. Issue 11 (November 2022) - Ogata, Hideyuki; Aoki, Nobumasa; Nagano, Kei; Hakamata, Mariko; Bamba, Yuuki; Shibata, Satoshi; Koizumi, Takeshi; Ohshima, Yasuyoshi; Watanabe, Satoshi; Moro, Hiroshi; Koya, Toshiyuki; Kikuchi, Toshiaki
Abstract: Introduction: This study aimed to examine the factors associated with cytomegalovirus (CMV) antigenemia and the time of onset of CMV antigenemia among patients with rheumatic diseases. Methods: A single-center, retrospective, observational study was conducted in our institution from January 2009 to December 2017. This study included patients with rheumatic diseases who had at least one CMV antigen measurement. Multivariate analysis and receiver operating characteristic analysis was performed. Results: A total of 249 patients underwent CMV antigenemia assay, and 84 (33.7%) patients tested positive. When the association between CMV antigenemia and possible associated factors was investigated, multivariate analysis showed that daily steroid dose increased the odds of having CMV [odds ratio 16.25, 95% confidence interval (CI), 5.360–49.253]. In this study, the cutoff value of daily steroid dose found in this study (0.45 mg/kg/day) was reasonable in clinical practice, and the area under the curve of the steroid dose was 0.838 [95% CI 0.781–0.882], which was the largest of the known indicators. Moreover, the median time from the start of immunosuppressive therapy to the onset of CMV antigenemia was 30 (interquartile range, 21–44) days, and most of the daily steroid users (85.7%) developed CMV antigenemia within 60 days. Conclusions: The daily steroid dose is the most important factor associated with CMV antigenemia. Therefore, monitoring and treatment strategies based on the steroid dose, especially in the initial 2 months, are important.